Avatar-based patient monitoring in critical anaesthesia events: a randomised high-fidelity simulation study. (May 2021) - Roche, Tadzio R.; Said, Sadiq; Braun, Julia; Maas, Elise J.C.; Machado, Carl; Grande, Bastian; Kolbe, Michaela; Spahn, Donat R.; Nöthiger, Christoph B.; Tscholl, David W.
Abstract: Background: Failures in situation awareness cause two-thirds of anaesthesia complications. Avatar-based patient monitoring may promote situation awareness in critical situations. Methods: We conducted a prospective, randomised, high-fidelity simulation study powered for non-inferiority. We used video analysis to grade anaesthesia teams managing three 10 min emergency scenarios using three randomly assigned monitoring modalities: only conventional, only avatar, and split-screen showing both modalities side by side. The primary outcome was time to performance of critical tasks. Secondary outcomes were time to verbalisation of vital sign deviations and the correct cause of the emergency, perceived workload, and usability. We used mixed Cox and linear regression models adjusted for various potential confounders. The non-inferiority margin was 10%, or hazard ratio (HR) 0.9. Results: We analysed 52 teams performing 154 simulations. For performance of critical tasks during a scenario, split-screen was non-inferior to conventional (HR=1.13; 95% confidence interval [CI], 0.96–1.33; not significant in test for superiority); the result for avatar was inconclusive (HR=0.98; 95% CI, 0.83–1.15). Avatar was associated with a higher probability for verbalisation of the cause of the emergency (HR=1.78; 95% CI, 1.13–2.81; P =0.012). We found no evidence for a monitor effect on perceived workload. Perceived usability was lower for avatar (coefficient=–23.0; 95% CI, –27.2 to –18.8; P <0.0001) and split-screen (–6.7; 95% CI, –10.9 to –2.4; P =0.002) compared with conventional. Conclusions: This study showed non-inferiority of split-screen compared with conventional monitoring for performance of critical tasks during anaesthesia crisis situations. The patient avatar improved verbalisation of the correct cause of the emergency. These results should be interpreted considering participants' minimal avatar but extensive conventional monitoring experience.